Evaluating Designs for a Fiscal Rule in Bulgaria - Andritzky, Jochen (Washington, D.C. : International Monetary Fund, 2011)
The enhanced Stability and Growth Pact calls on euro area members and aspirants to set boundaries to fiscal deficits through high-level legislation. A limit on the deficit, such as the deficit ceiling in Bulgaria's organic budget law, serves to protect solvency. The recent crisis clearly indicated that the key challenges are not only to contain the deficit but also to avoid a procyclical stance during upswings and to build a buffer for rainy days. Ideally, fiscal policymaking is guided by a fiscal rule that adapts through the economic cycle. This paper lays out the objectives of fiscal rules and analyzes how these objectives can be met in Bulgaria through either a growth-adjusted balance rule or an expenditure rule complemented by a deficit ceiling.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet